Rauwolfia vomitoria- a promising medical plant for benign prostatic hyperplasia management; yet with challenges - George Awuku Asare; Perpetua Dagadu; Samuel Adjei; Bernice Asiedu; Samkeliso Takaidza; Vivash Naidoo; Brodrick Amoah; Ifeoma Celestina Orabueze; Kwasi Bugyei (Phytomedicine Plus)
Background: Benign Prostatic Hyperplasia (BPH) is a common condition among aging men. This condition often leads to a reduced quality of life due to its debilitating symptoms. Although conventional allopathic treatments are widely used for managing BPH, they are frequently associated with adverse side effects, prompting a global shift toward natural and alternative therapies. This study aims to investigate the therapeutic effects of Rauwolfia vomitoria Aqueous Root Extract (RVARE) as a potential natural oral treatment for BPH. Methodology: Six groups of male Sprague-Dawley rats were established [N = 7/group]. Group 1 comprised of normal rats whilst group 2 to group 6 comprised of BPH induced rats. Group 1: Control group- received normal chow diet. Group 2: Model group- [no treatment]. Group 3: received 10 mg/kg. b. wt. RVARE. Group 4: received 25 mg/kg. b.wt. RVARE. Group 5: received 50 mg/kg. b.wt, RVARE. Group 6: served as a positive control [Finasteride]. The study was carried out for 28 days. Upon termination, blood was sampled for general biochemical, haematological and PSA determination. Systemic organs and the prostate were harvested for histological analyses. Result: Histopathological analysis of the liver of RVARE treated groups demonstrated alterations. Additionally, a reduction in relative prostate weight compared to the model group was observed, though not statistically significant (p > 0.05). However, a significant reduction in prostate specific antigen (PSA) levels was seen in the RVARE-treated groups (Model vs Gp 3, p = 0.001; Model vs Gp 4, p = 0.000; Model vs Gp 5, p = 0.001). Conclusion: RVARE appears to be effective in reducing prostate size and PSA levels. However, its hepatotoxic effect needs further investigation.